FEAR AND LOATHING IN NORTHERN JOHANNESBURG: THE SECURITY PARK AS HETEROTOPIA. - Hook, Derek; Vrdoljak, Michele (PINS-Psychology in Society, 2026)
This is somewhat of an unconventional paper. It is essentially a "sketching of ideas", a speculative generation of hypotheses that precedes a larger empirically-based research project on identity and space in the South African security park. It opens with a brief discussion of how space - much like discourse more widely - is able to inform identity. It then moves onto a focus on the South African security park, that exclusive and affluent living space so favoured by the inhabitants of Northern Suburban Johannesburg. Foucault's conception of the heterotopia is applied to this focus as a means of exploring (and generating hypotheses around) the inter-relatedness of the categories of space, power and identity. The paper turns then to briefly consider the shortcomings of the notion of the heterotopia, before closing by asserting a series of general (and hypothetical) conclusions about the apparent interconnectedness of power, space and identity in such a place as the security park.